Safety evaluation of some newer pesticides against lac insect, Kerria lacca (Kerr) for managing lac insect-predators in lac ecosystem - Singh, J P; Jaiswal, A K; A, Md Monobrullah (The Indian Journal of Agricultural Sciences, 2012)
The current prosperity in the lac market provides an incentive for farmers to increase lac production. In order to increase lac production, it is important to manage the insect predators and parasitoids associated with lac insect which is playing a key limiting factor in attaining optimum lac productivity and sustained lac production. Seven newer insecticides viz., indoxacarb, spinosad, fipronil, lambdacyhalothrin, alphamethrin, bifenthrin and carbosulfan alongwith two already recommended insecticides namely ethofenprox and endosulfan have been evaluated against first and second larval stages of lac insect for its safety, so that it can be further assessed for their bioefficacy against harmful biotic fauna associated with lac insect. Insecticides namely spinosad (0.0025%, 0.005%, 0.01%, 0.02%), indoxacarb (0.003%, 0.005%, 0.007%, 0.01%, 0.02%), fipronil (0.0025%, 0.005%, 0.01%) and carbosulfan (0.01%, 0.02%) have been found safe against first and second instar larvae of both kusmi and rangeeni strain of lac insect under field conditions. Lambdacyhalothrin, alphamethrin and bifenthrin were found safe to lac insect at lower concentrations, but detrimental effect on growth and development of lac insect was observed with increase in dosages, hence may not be suitable for application at the initial stage of crop development (first application) in lac production system. It is suggested that newer compounds like spinosad (0.005%) which is a naturalyte synthetic analogue compound produced by fermentation of a rare bacterium, Sacharopolyspora spinosa, indoxacarb (0.005%), fipronil (0.005%) and carbosulfan (0.01%), with different mode of action and whose safety against lac insect has been evaluated and established at some higher concentrations also, can be incorporated in pest management programme to achieve the desired control of lac insect predators in lac production system without harming lac culture.